The plantar proximal cortex of the third metatarsal bone shows raised longitudinal ridges at the suspensory ligament enthesis in normal equine isolated limbs – a radiographic, computed tomography, and MRI study - Dancot, Michaël; Joostens, Zoë; Audigié, Fabrice; Busoni, Valeria (Frontiers in Veterinary Science, 2023)
This is a provisional file, not the final typeset articleLimbs were normal at MR imaging. Longitudinal linear ridges were present on the proximal plantar metatarsal surface in all limbs (1-2 sagittal ridges, 1 ridge located at medial or lateral margin of the suspensory ligament). Longitudinal ridges were positioned facing an adipo-muscular bundle of the suspensory ligament on CT images and were visible as linear increased opacities on dorsoplantar radiographs. Delineation of the trabecular/cortical interface of the proximal metatarsus changed with radiographic projection and was the sharpest on the plantaro85°lateral to dorsomedial oblique view.The proximal third metatarsal bone shows morphological individual variations with longitudinal linear ridges that alter the bone homogeneity on dorsoplantar radiographs. An oblique plantaro 85°lateral to dorsomedial view is suggested to better assess the presence of subcortical sclerosis when a proximal suspensory enthesopathy is suspected.